Severe digital malformations in a rare variant of fibrodysplasia ossificans progressiva. Issue 7 (22nd April 2019) - Gucev, Zoran; Tasic, Velibor; Plaseska‐Karanfilska, Dijana; Dimishkovska, Marija; Laban, Nevenka; Bozinovski, Zoran; Kostovski, Marko; Saveski, Alek; Polenakovic, Momir; Towler, O. Will; Shore, Eileen M.; Kaplan, Frederick S.
Abstract: A 16‐year‐old girl with a history of nontraumatic swelling of both forearms, osteochondromas of the knees, heterotopic ossification of the neck and back, severe malformations of all digits with hypoplastic or absent nails, alopecia partialis of the scalp, and moderate cognitive impairment was seen for diagnostic evaluation. Whole exome sequencing identified an activating mutation of ACVR1 (c.983G > A; p.Gly328Glu) which confirmed a suspected FOP variant. The delayed diagnosis of an FOP variant in this patient could have been avoided if the significance of severe digital malformations had been recognized, especially in the setting of progressive heterotopic ossification.